PENGEMBANGAN MODEL PEMBELAJARAN LARI CEPAT PADA SISWA SEKOLAH DASAR - Almunawar, Ahmad (STOK BINA GUNA MEDAN, 2017)
In general, the purpose of this research and development was to produce a learning model of sprint on elementary school students. The development research was user a model of Research & Development (R & D) approach of Brog and Gall. The subjects of the research and development were 35 male of fifth grader students in Duren Sawit 13 Elementary School, East Jakarta.In testing the effectiveness of the development of this sprint learning model can be seen from the psychomotor data. The effectiveness level of the previos teaching model was 66% of the expected criteria. While the effectiveness level of a new learning model is was 76% of the expected criteria, it meant that there was an increase of 10%.Based on this study, it can be concludedthat: (1) learning model of sprint through games canimprove the multilateralmovementon students, (2) the learning model was more effective and efficient in order to increase students interestandmotivationinlearningphysical education.